Pewarnaan Graf Dalam Penentuan Jadwal Ujian Mahasiswa (Studi Kasus Prodi Teknik Informatika Unwidha) - Niken Retnowati; Aryati Wuryandari; Agustinus Suradi (UJMC (Unisda Journal of Mathematics and Computer Science), 2025)
Often, scheduling final-year student exams becomes a problem within the scope of study programs, one of which is the Informatics Engineering study program at Widya Dharma University, Klaten. This is because the schedule of each examining lecturer is not the same, and besides that, the space available also varies every day. There are several alternative algorithms that can be used to solve scheduling problems, one of which is graph coloring. Graph coloring can include points, lines, and areas. In this research, researchers will try to divide student exam schedules using dot coloring, where the dot coloring algorithm used is Welch Powel The Welch Powell algorithm is the most frequently used graph coloring algorithm. This algorithm starts by sorting the degrees of the graph from largest to smallest, then assigns a color to the vertex at the largest vertex and assigns a different color to the vertices below that are not adjacent to that vertex. Keywords: Welch-Powell algorithm, graph, graph coloring.